The Comparative Performance between Islamic and Conventional Unit Trust Fund in Malaysia - Nurlina Binti, Razali; Sharifah Sabrina, Syed Ali; Mohd Waliuddin, Mohd Razali (2015)
This study is to examine the performance between the Islamic unit trust funds and the conventional trust funds in Malaysia. The objectives of the study were to compare the nature and characteristics of both funds, assess their risks and returns profiles, measure the degree of diversification, compare the consistency of performance ranking and do the correlation analysis. The performance of both funds were analyzed over a period of 96 months commencing from January 2006 to December 2013 and evaluated based on the standard performance measures for funds known as Adjusted Sharpe, Treynor and Adjusted Jensen Alpha Indices. The composite index of the Kuala Lumpur Stock Exchange (KLSE) represented the market benchmark for the conventional funds while the Islamic fund used Syariah index as proxy for the market. The findings revealed that on average, for non-crisis period the Islamic funds are underperformed the conventional unit trust fund. However, during and after crisis period, Islamic fund outperformed the Conventional unit trust funds